FACTORS ASSOCIATED WITH SCABIES IN SANTRI AT THE MA'HAD DAARUT TAHFIZH AL-IKHLAS ACEH BESAR ISLAMIC BOARDING SCHOOL - Zaafira, Zaafira; Laweung, Ibrahim; Santi, Tahara Dilla (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Scabies is a parasitic infection of the skin caused by Sarcoptes scabei var hominis with complaints of itching, especially at night, which is characterized by skin abnormalities in the form of papules, vesicles, urticaria, and cristae and is often experienced by students in Islamic boarding schools. Method: The design of this research is descriptive-analytic with a cross-sectional approach. The population in this study were all female students at the Ma'had Daarut Tahfizh Al-Ikhlas Aceh Besar Islamic boarding school in 2020, totaling 136 female students. The sample in this research was all female students, totaling 136 female students. Data collection was carried out from 5-14 April 2021 using questionnaires through interviews. Data analysis used the Chi-Square test with the SPSS 21 program. Result: The results showed that there was a relationship between knowledge (p=0.005), personal hygiene (p=0.002), behavior (p=0.005 ), health officer visit (p=0.024), health services (p=0.038 ), and the role of ustadzah in health information (p=0.015) with scabies and there was no relationship between routine examinations and scabies (p=0.084). Recommendation: It is hoped that local health workers will be more active in educating female students about scabies and how to prevent it.